KONSEP MASLAHAH MAXIMIZER PADA HOTEL SYARIAH PERSPEKTIF ETIKA BISNIS ISLAM - Ghufron, Moh Idil (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
This paper aims to examine the concept of maslahah maximizer in sharia hotels in the perspective of Islamic business ethics. As is known, in the behavior of a manufacturer in general, in improving the competitiveness of products, a producer is competing to find a strategy to achieve maximum profits, so as to gain high profits, which affects the realization of welfare, both individually and members. The reality that happens, to realize the welfare, the company in this, the hotel manager justifies all means, offer worldly satisfaction and beautify the interior of the room, to be able to get the maximum profits. There are several factors that are not ignored by the company in maximizing profits, namely; safety factors, financial transparency, convenience of purity, kosher or not food. Sharia hotels appear in the midst of the concerns of tourists in terms of security and comfort, especially, business motivation undertaken by sharia hotels, aims to promote the benefit of funds maximize income